The Use of Percutaneous Naviculocuneiform Arthrodesis to Restore Medial Column Stability in Flatfoot Reconstruction: Techniques and Outcomes - Shuyuan Li MD, PhD; Christopher Hurry MD; James Ryeburn BSc; Alastair S.E. Younger MB ChB, ChM, FRCSC (Foot & Ankle Orthopaedics)
Category: Midfoot/Forefoot; Hindfoot Introduction/Purpose: Through years of experience in correcting flatfoot deformities, the senior author has recognized that the Naviculocuneiform (NC) joint arthrodesis is a powerful procedure in flatfoot reconstruction. It directly addresses the arch collapsing distal to the talonavicular joint. It can de-rotate the mid and forefoot pronation across both the medial and middle columns and therefore can be more effective than a Cotton osteotomy or 1st TMT arthrodesis which only includes the medial column. In severe flexible flatfoot deformities, NC arthrodesis combined with 1st TMT arthrodesis, lateral column lengthening, and muscle balancing can achieve correction without sacrificing the motion of the hindfoot. This study introduces a novel technique of percutaneous NC arthrodesis with non-compression subchondral fixation, with conjunctive procedures to restore the medial arch, and its outcomes. Methods: Between 2019 and 2023, 22 percutaneous NC arthrodeses were performed for flatfoot reconstruction (detailed procedures see Table 1). The procedure included the use of a beaver blade to establish 3 portals(dorsomedial, middle, and lateral) under fluoroscopic guidance. A 2 x 12mm MICA burr was used with or without the supervision of a 3.5mm arthroscope to remove the cartilage from the three NC facets but keep the subchondral bone. The arthroscope and a shaver were then used to check and complete cartilage removal. A pin distractor was used to enlarge the joint space, and de-rotate the NC joint (plantarflex, adduct, pronate) during fixation. Multiple fully threaded 4 mm screws were used to transfix the subchondral bone without compression and maintain subchondral bone fixation, which has been proven to have a much stronger effect than plate and compression fixation in another study from our group ref1. Results: The average surgical time for the percutaneous NC arthrodesis was 20 minutes. For the 22 cases, the mean age was 60 years old (21-86). Comorbidities included diabetes (4), obesity (3), renal transplant (1), osteoporosis (1), rheumatoid arthritis (1), a prior first TMT nonunion (1), and prior hindfoot arthrodesis (2). No bone graft was used. The average union time was 3 months and a 100% union rate was achieved based on plain imaging or CT scan. The arch height ratio (height of medial cuneiform/5th metatarsal base) was improved from 1.11 to 1.53, a 46.8% improvement, the pitch angle was improved from 12.39 to 15.39 degrees (24.2%), and the lateral Meary’s angle was improved from -19.58 to -7.71 degrees (60.1%). Conclusion: Percutaneous NC arthrodesis with subchondral fixation has a high fusion rate, is easy to perform although associated with a learning curve, and includes the advantages of minimally invasive surgery. Percutaneous NC fusion in isolation can be used for arthritis of the NC joint. Percutaneous NC fusion can be combined with other procedures, such as arthroscopic subtalar fusion, percutaneous TMT fusion, or open lateral column lengthening in the correction of deformity of the foot associated with flat foot deformity. Reference 1: Comparison of percutaneous Lapidus intraosseous screws versus open plate fixation for first tarsometatarsal fusion - a matched cadaver study.